Production of a new generation of leptons in hadronic collisions - Éboli, O. J P [UNESP]; Marques, G. C.; Novaes, Sérgio Ferraz [UNESP]; Natale, A. A. (Elsevier, 1986)
The contribution is studied of vector boson fusion processes to the production of a heavy charged lepton accompanied by its neutral partner at multi-TeV hadronic colliders. It is shown that vector boson fusion dominates over the usual quark-antiquark fusion mechanism for a very heavy lepton and high energies. © 1986.